Plant Exosome-like Nanovesicles: Emerging Therapeutics and Drug Delivery Nanoplatforms - Dad, Haseeb Anwar; Gu, Ting-Wei; Zhu, Ao-Qing; Huang, Lu-Qi; Peng, Li-Hua (Molecular therapy, 2021)
Plant exosome-like nanovesicles, being innately replete with bioactive lipids, proteins, RNA, and other pharmacologically active molecules, offer unique morphological and compositional characteristics as natural nanocarriers. Furthermore, their compelling physicochemical traits underpin their modulative role in physiological processes, all of which have fostered the concept that these nanovesicles may be highly proficient in the development of next-generation biotherapeutic and drug delivery nanoplatforms to meet the ever-stringent demands of current clinical challenges. This review systemically deals with various facets of plant exosome-like nanovesicles ranging from their origin and isolation to identification of morphological composition, biological functions, and cargo-loading mechanisms. Efforts are made to encompass their biotherapeutic roles by elucidating their immunological modulating, anti-tumor, regenerative, and anti-inflammatory roles. We also shed light on re-engineering these nanovesicles into robust, innocuous, and non-immunogenic nanovectors for drug delivery through multiple stringent biological hindrances to various targeted organs such as intestine and brain. Finally, recent advances centered around plant exosome-like nanovesicles along with new insights into transdermal, transmembrane and targeting mechanisms of these vesicles are also elucidated. We expect that the continuing development of plant exosome-like nanovesicle-based therapeutic and delivery nanoplatforms will promote their clinical applications.